Marketing digital na hotelaria: estudo de caso no Farol Hotel de Arroio Grande/RS - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The present work focuses on digital marketing through an analysis of services and the market, having as a study environment a hotel located in the municipality of Arroio Grande/RS. The objective of this work is to understand the importance of digital marketing in current times and how a company in the hospitality sector can adapt digital marketing strategies in order to communicate effectively with its customers and also with its possible target audience. It is an opportunity to promote tourism in the municipality and region, especially through digital marketing strategies and to differentiate itself from the competition. To this end, collaboration with the hotel management was sought, through qualitative, applied and documental research, with descriptive objectives, through a case study, in order to analyze the services provided and propose a digital marketing plan focused on on the social networks. General aspects of marketing and digital marketing, based on bibliographical studies, were approached to support the study. For data collection, interviews were conducted with the owners of the Farol Hotel, observation and analysis of the local services, as well as the social media used by direct competitors, located in Arroio Grande/RS. Based on the research results, it was possible to draw up a digital marketing plan and verify the feasibility of application in the hotel. It is understood that the practical activities that the hotel will be able to carry out, in relation to digital marketing, will be able to help in greater visibility and demand, in addition to promoting tourism in the city of Arroio Grande/RS and region.
Keywords: Marketing; Marketing Digital; Hotelaria; Farol Hotel; Arroio Grande, RS; Marketing; Digital Marketing; Hospitality; Farol Hotel; Arroio Grande, RS; CNPQ::CIENCIAS SOCIAIS APLICADAS